HOW FEMINIST CRIMINOLOGY SHAPES LEGISLATIVE REACTION TO FAMILIY VIOLENCE IN SERBIA - Samardžić, Stefan; Ristivojević, Branislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Author deals with a problem of a justification of the leading ideas that inspired new Code on Prevention of Family Violence in Serbia. Author proofs assumption that the Code is grounded on a basic premisses of the, so called, radical feminist criminology regarding family violence. After short retrospect to elementary rules of a scientifically founded criminal policy, in the second part author exhibit the origin of this legislative solution. Out of it becomes clear that this is a piece of legislation special to totality of legal system which bears the burden of a suppression of family violence in Serbian society, whose substance was compiled by the group of NGO of a radical feministic orientation. In the third, central part of the paper, author proofs the origin of a specific doctrines in the Code by comparison with key tenets of this extreme and radical school of criminological thought. Author concludes that they are nothing more but an unscientific attempt to shroud radical feministic ideas behind a mask of a scientific discipline – ethology of a crime. At the very end author illustrated aforementioned comparison with negative effects of a Code to family in Serbian society. In the same time author criticise total legislative indifference toward prevailing culture and values of a society in which the Code should apply.